Anticancer Properties of Different Solvent Extracts of Cucumis melo L. Seeds and Whole Fruit and Their Metabolite Profiling Using HPLC and GC-MS. (26th February 2020) - Zhang, Xudong; Bai, Yuzhuo; Wang, Yun; Wang, Chunlan; Fu, Jianhua; Gao, Longlan; Liu, Yu; Feng, Jingbin; Swamy, Mallappa Kumara; Yogi, Maddipatla; Rudramurthy, Gudepalya Renukaiah; Purushotham, Boregowda; et al.
Abstract : Honeydew melon ( Cucumis melo L.) is an oval-shaped delicious fruit of one cultivar group of the muskmelon with immense nutritional importance and is extensively consumed by many tropical countries. The effect of various organic solvents on the recovery of phytochemicals from honeydew melon plant fruits and seeds was assessed. Further, High-Performance Liquid Chromatography (HPLC) was used to examine and assess the contents of phenolic acid (gallic acid) and flavonoid (rutin) compounds. The use of gas chromatography–mass spectrometry (GC-MS) analysis explained the presence of volatile phytocompounds in the extracts. The use of organic solvents had a substantial impact on the total dry weight and extract yield. In general, the solvent-extracted constituents remained in the order of methanol>chloroform>distilled water for both honeydew melon seeds and whole fruit. 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) was used to assess the cytotoxicity effect against PC3, HCT116, HeLa, and Jurkat cell lines. The chloroform extract exhibited a good cytotoxic activity against all cell lines as compared to other solvent extracts. HPLC analysis revealed the occurrence of gallic acid content of 0.102 ± 0.23 mg/10 mg of dry whole fruit extract, while 10 mg of dry seed extract contained only 0.022 ± 0.12 mg of gallic acid content. Likewise, rutin content was observed to be 0.224 ± 0.31 mg and 0.1916 ± 0.82 mg/10 mg of dry whole fruit and seed extract, respectively. Further, GC-MS analysis revealed the presence of a total of 37 compounds in chloroform extract of whole fruit, while only 14 compounds were found in seed extract. Nevertheless, more examinations are needed to identify and characterize other metabolites from honeydew melon and evaluate their pharmacological importance.